INOVASI DAN MODERNISASI PENDIDIKAN ISLAM DI SEKOLAH BOARDING - Moh. Hifzul Muiz; Agus Salim Mansyur; Qiqi Yuliati Zaqiah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Indeed, innovation and modernization of Islamic education is very necessary and must be carried out continuously. Because with the innovation and modernization in Islamic education, it will provide a positive value for an Islamic educational institution itself, including boarding schools. Studies on innovation and modernization of Islamic education in boarding schools are often found in various forms. The study of innovation and modernization of Islamic education in boarding schools is very interesting because it contains several important elements, first, it is a study that is relevant to the goals of Indonesian education which is in the process of developing education and modernization; second, it can give its own color in Indonesian education; third, it will give birth to an ideal education model for the Indonesian people because it integrates the cognitive, affective and psychomotor domains. In this case, boarding schools have an important role in the innovation and modernization of Islamic education. Because until now they have not stopped innovating and modernizing, so that boarding schools can continue to adapt to innovation and modernization of education in Indonesia. There is a fundamental difference between innovation and modernization which emphasizes the characteristics of each. Innovation emphasizes the characteristics of something that is observed as something new for individuals or society, while modernization emphasizes the process of change from traditional to modern, or from undeveloped to modern. already advanced. In the current context of Islamic education, there are at least three important aspects in relation to modernization, innovation, namely in the aspects of methods, content and management.